Hello Professor : A Black Principal and Professional Leadership in the Segregated South - Walker, Vanessa Siddle (Book collections on Project MUSE., 2009)
Like many black school principals, Ulysses Byas, who served the Gainesville, Georgia, school system in the 1950's and 1960's, was reverently addressed by community members as ""Professor."" He kept copious notes and records throughout his career, documenting efforts to improve the education of blacks. Through conversations with Byas and access to his extensive archives on his principalship, Vanessa Siddle Walker finds that black principals were well positioned in the community to serve as conduits of ideas, knowledge, and tools to support black resistance to officially sanctioned regressive education.